Full Genome Evolutionary Studies of Wheat Streak Mosaic-Associated Viruses Using High-Throughput Sequencing - Redila, Carla Dizon; Phipps, Savannah; Nouri, Shahideh (Frontiers in Microbiology, 2021)
Wheat streak mosaic (WSM), a viral disease affecting cereals and grasses, causing substantial losses in crop yields. Wheat streak mosaic virus (WSMV) is the main causal agent of the complex, but mixed infections with Triticum mosaic virus (TriMV) and High plains wheat mosaic emaravirus (HPWMoV) were reported as well. Although resistant varieties are effective for the disease control, a WSMV resistance-breaking isolate and several potential resistance-breaking isolates have been reported, suggesting that viral populations are genetically diverse. Previous phylogenetic studies of WSMV were conducted by focusing only on the virus coat protein (CP) sequence, while there is no such study for either TriMV or HPWMoV. Here, we studied the genetic variation and evolutionary mechanisms of natural populations of WSM-associated viruses mainly in Kansas fields and fields in some other parts of the Great Plains using high-throughput RNA sequencing. In total, 28 historic and field samples were used for total RNA sequencing to obtain full genome sequences of WSM-associated viruses. Field survey results showed WSMV as the predominant virus followed by mixed infections of WSMV+TriMV. Phylogenetic analyses of the full genome sequences demonstrated that WSMV Kansas isolates are widely distributed in sub-clades. In contrast, phylogenetic analyses for TriMV isolates showed no significant diversity. Recombination was identified as the major evolutionary force of WSMV and TriMV variation in KS fields, and positive selection was detected in some encoding genomic regions in the genome of both viruses. Furthermore, the full genome sequence of a second Kansas HPWMoV isolate was reported. Here, we also identified previously unknown WSMV isolates in the Great Plains sharing clades and high nucleotide sequence similarities with Central Europe isolates. The findings of this study will provide more insights into the genetic structure of WSM-associated viruses and in turn, help in improving strategies for disease management.